Form of Presentation and Character Value on Nayakatama Dance - Diah Purwandari; Kusnadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the form of presentation of the Nayakatama dance and its character values originating from the Special Region of Yogyakarta. This study includes the form of presentation and character values in the Nayakatama dance. Nayakatama Dance, one of the Yogyakarta Style dance dramas. This study uses a qualitative approach and ethnographic methods. The data collection techniques are observation, interviews, and documentation studies. The instruments used for data collection were observation sheets, interview guides, and documentation guides. The data is validated using interviews with informants. The resource person in this study is the creator of the Nayakatama dance. The results of the study concluded that the form of presentation of the Nayakatama Dance originates from the Mahabharata story, namely the story of Arjuna Wiwaha. In the performance, it is danced in the form of bedhayan, namely by nine dancers, one person as Raden Arjuna, one person as Prabu Newatakawaca, one person as Dewi Supraba and six people as Rampak Putri. This dance contains character values that exist in humans, that greed, greed, arrogance, and all ambitions that are achieved in a way that is not good can bring disaster. Only humans who have a clean soul, who are not tempted by the splendor of the world, can eradicate bad traits, that is the human being needed to maintain world peace and eternity